Unleashing the potential of eHealth in outpatient cancer care for patients undergoing immunotherapy—a quantitative study considering patients’ needs and current healthcare challenges - Holderried, Tobias A. W.; Stasik, Isabel; Schmitz, Marie-Therese; Schmitz, Friederike; Meyer, Tizian K.; Stauß, Leonie; Kirschner, Martin; Skowasch, Dirk; Landsberg, Jennifer; Schmid, Matthias; Brossart, Peter; Holderried, Martin (Frontiers in Digital Health, 2024)
BackgroundThe use of online information and communication is globally increasing in the healthcare sector. In addition to known benefits in other medical fields, possible specific potentials of eHealth lie in the monitoring of oncological patients undergoing outpatient therapy. Specifically, the treatment with immune checkpoint inhibitors (ICI) requires intensive monitoring due to various possible negative side effects. The present study explores cancer patients’ perspectives on eHealth and demonstrates how eHealth applications, from the patients’ point of view, can contribute to further improving outpatient immunotherapy.Methods and findingsOur multicenter study was executed at the university hospitals in Bonn and Aachen. A structured questionnaire was distributed to patients receiving outpatient immunotherapy. Contents addressed were (1) the patients’ attitude towards eHealth applications, (2) the use of modern information and communications technologies (ICT) in (2a) everyday life and (2b) health-related information search including eHealth literacy, (3) the use of internet-enabled devices as well as (4) socio-demographic data. 164 patients were included in the study, of whom 39.0% were female and 61.0% male and the average age was 62.8 years. Overall, there was a high distribution of internet-enabled devices for everyday use and a great interest in integrating eHealth applications into outpatient immunotherapy. The assessment of eHealth potentials significantly depended on age. The younger participants demonstrated a broader use of modern ICT and a higher affinity for its use in outpatient immunotherapy. In some aspects, level of education and gender were also relevant factors influencing the patients’ view on eHealth.ConclusionThis study demonstrates the potential for further integration of eHealth applications into outpatient immunotherapy from the patients’ perspective. It indicates a dependency on age and educational level for the further integration of eHealth into patient care in oncology. Due to particular patient needs regarding age, level of education, gender and other subgroups, specific education and training as well as target-group specific digital health interventions are necessary to fully utilize the potentials of eHealth for outpatient immunotherapy. Future studies are required to specifically address target-group specific usability of eHealth applications and eHealth literacy, as well as to address information security and data protection.